2017
DOI: 10.1007/s00221-017-4959-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vestibular disorders on vestibular reflex and imagery

Abstract: The aim of this study was to establish the effect of vestibular lesion on vestibular imagery. Subjects were required to estimate verbally their passively travelled rotation angles in complete darkness, i.e., to activate vestibular imagery. During motion, the vestibulo-ocular reflex (VOR) was measured. Thus, we examined the coherence between the vestibulo-ocular reflex and self-rotation imagery, with vestibular-lesioned patients and healthy participants. Unilateral acute and chronic patients, bilateral patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The first observation was that the patient group showed normal position and velocity/acceleration perception. A previous experiment with repetitive rotations from 90 • to 360 • with a 90 • interval showed that patients with acute and chronic unilateral vestibulopathy had intact position estimates in ipsilesional and contralesional rotations (Cohen et al, 2017). Therefore, the position estimation in this study using more fractionalized intervals reaffirmed the previous findings.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The first observation was that the patient group showed normal position and velocity/acceleration perception. A previous experiment with repetitive rotations from 90 • to 360 • with a 90 • interval showed that patients with acute and chronic unilateral vestibulopathy had intact position estimates in ipsilesional and contralesional rotations (Cohen et al, 2017). Therefore, the position estimation in this study using more fractionalized intervals reaffirmed the previous findings.…”
Section: Discussionsupporting
confidence: 88%
“…Of interest, the VOR pathway remained compromised in previous and current studies (Cousins et al, 2013;Cohen et al, 2017), which could support that the recovery of the VP pathway is more robust than that of the VOR pathway. The VP and VOR pathways have been known to share a velocity storage circuit (Bertolini et al, 2012).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This can even take place at the cortical level, as shown in a parabolic flight study ( Demertzi et al, 2015 ; Van Ombergen et al, 2017 ). Similar inhibition of VOR gains during rotation to the healthy side are observed in the early phase of a vestibular neuritis in dizzy patients to limit the degree of asymmetry ( Cohen et al, 2017 ). This could be a first reason why the OCR is reduced during centrifugation compared to a static body or head tilt.…”
Section: Discussionmentioning
confidence: 58%
“…Recovery, after return to Earth, takes some time during which there is a readaptation of the otolith function to the Earth's gravitational level of 1 g take place (Kornilova et al, 2012(Kornilova et al, , 2017. It is known that in these recovery processes, the nodulus and uvula of the cerebellum play an important role (Cohen et al, 2002(Cohen et al, , 2019.…”
Section: Discussionmentioning
confidence: 99%